Morphological evidence that high density lipoproteins are not internalized by steroid-producing cells during in situ organ perfusion. - Reaven, E (1984)
Although it is clear that high density lipoproteins (HDL) can support steroidogenesis in several rat cell systems, questions still arise as to how HDL are processed by cells. In particular, it is not yet clear whether HDL are internalized by a pathway similar to that used for low density lipoproteins. This issue was examined in the present study using the luteinized ovaries of hormone-primed immature rats in an in situ perfusion system. Ovaries were perfused for 2-120 min with 125I-labeled human or rat HDL and processed for autoradiographic studies at the light and electron microscopic level, or homogenized and used for isolation of subcellular membranes. The results show that the luteal cells of this tissue bind both human and rat HDL with great specificity. Moreover, the intact HDL particle does not appear to be internalized by the luteal cell during the period of perfusion: i.e., the protein moiety of the labeled HDL remains associated with the plasma membrane at all times. Evidence from the autoradiographs suggest, however, that with time, an increasing proportion of the plasma membrane-bound protein is associated with inverted microvilli, which are embedded within the cytoplasm and make close contact with structures of the interior of the cell. We speculate that HDL-cholesterol may be transferred at such sites.